Isolation and Characterization Of Arbuscular Mychorhiza Fungi from Gaharu Wood (Aquilaria spp.) Rhizosphere - Dian Rachma Wijayanti; Maman Turjaman (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
In the last 30 years there have been increasing demand of agarwood. Unlimited hunting of agarwood causing it become threatened species. Aquilaria spp. is the main genus producing agarwood that considered as threathened species. Conserving Aquilaria spp. as germ plasm needs is essential against destruction. Arbuscular mycorrhizal fungi (AMF) have been used as inoculant to increase the growth of Aquilaria spp., but information about the existence of AMF in Aquilaria spp. rhizosphere has not been reported. This research was carried out with objective to identify AMF from Aquilaria spp. rhizosphere. Soil and root samples from rhizosphere of Aquilaria spp. taken from four location that is: Carita (A. malaccensis), Ciapus (A. filaria), Cifor (A. crasna & A. malaccensis), and Bantar Kemang (A. beccariana, A. crasna, & A. malaccensis). Roots staining was conducted with modified Phillips and Hayman procedure (1970). Soils sample was run dry wed and placed in pot culture with Pueraria javanica as the host plant. Spore was separated from pot culture using wet sieving and decanting method continued with centrifugation. The result showed the occurrences of AMF in Aquilaria spp. roots i.e. external hypha, internal hypha, coiled hypha, arbuscules, and vesicles. All AMF colony structure found in Aquilaria spp. roots show asosiation bettwen the plant and AMF. Four species of AMF were found i.e. Glomus sp.1, Glomus sp.2, Gigaspora albida, and Dentiscutata sp. Key Words: Isolation, Arbuscule Mycorrhizae Fungi, Rhizosfer, Agarwood